2023
DOI: 10.3390/ma16124236
|View full text |Cite
|
Sign up to set email alerts
|

The Wrinkles Characterization in GFRP Composites by Infrared Active Thermography

Abstract: An experimental study has been carried out to assess the effectiveness of infrared thermography in wrinkle detection in composite GFRP (Glass Fiber Reinforced Plastic) structures by infrared active thermography. Wrinkles in composite GFRP plates with different weave patterns (twill and satin) have been manufactured with the use of the vacuum bagging method. The different localization of defects in laminates has been taken into account. Transmission and reflection measurement techniques of active thermography h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…This is particularly important for curved samples. Our previous studies [7] demonstrated the effectiveness of thermography in detecting wrinkles in flat glass laminate structures and curved thin-walled structures, such as wind turbine blades. The results of thermography studies for reflection and transmission techniques were the subject of much discussion in those studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is particularly important for curved samples. Our previous studies [7] demonstrated the effectiveness of thermography in detecting wrinkles in flat glass laminate structures and curved thin-walled structures, such as wind turbine blades. The results of thermography studies for reflection and transmission techniques were the subject of much discussion in those studies.…”
Section: Discussionmentioning
confidence: 99%
“…in the form of fiber waviness and wrinkles in laminates, ultrasonic inspection [5,38], eddy current method [39], and infrared thermography [7] are used.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations